Develop A Set of Health-Improving Exercises for Middle-Aged 45-60-Year-Old Men, Considering Physical Fitness - Xurramovich, Karimov Faxriddin; Qaxhorovich, Shermatov Gulom; Mukhametovich, Mukhametov Ahmad; Napasovich, Kholmuratov Ravshan; Alisherovich, Tashpulatov Farxad (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses the development of a set of fitness exercises for middle-aged men, taking into account physical fitness, including in-depth study of the elements of exercise, games and sports based on physical condition, health, interests and desires, their implementation analyzes the choice of paths according to practical preference.